Innovations in food packaging - Han, Jung H. (Food science and technology international series., 2005)
Packaging performs a number of functions in the containment, protection, shipment and selling of goods. Innovations in Food Packaging recognizes that food packaging is a fast-growing area that impacts upon the important areas of product shelf-life and food safety. Each chapter provides information on the scientific background, new material development and utilization, and case studies of the use of new system for perishable food products. Covers four major food packaging topics: * Theories in food packaging * Active packaging * Modified atmosphere packaging * Edible films and coatings.